Associations between PIK3CA Mutations and Disease Free Survival in Patients with HR+, HER2− Tumors Treated with Adjuvant Hormonal Therapy: A Real-World Study in Croatia - Dora Čerina Pavlinović; Natalija Dedić Plavetić; Ingrid Belac Lovasić; Robert Šeparović; Josipa Flam; Marija Pancirov; Žarko Bajić; Snježana Tomić; Eduard Vrdoljak (Wiley, 2024)
Introduction. Disease recurrence in patients with the early hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2−) breast tumor subtype is particularly challenging to manage due to its complex and very heterogeneous biological nature. Namely, due to primary and secondary resistance, one-quarter of patients with early-stage disease will experience disease recurrence. This variability in the timing of recurrence highlights the need to better identify key biomarkers that could predict therapeutic outcomes and guide personalized treatment strategies for these patients. Mutations in the phosphatidylinositol 4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) gene are highly prevalent (30-40%) in HR+/HER2− advanced breast cancer. They lead to activation of the PI3K/AKT/mTOR pathway, promoting cell growth, and proliferation, and are associated with poor prognosis in advanced breast cancer. Our aim was to examine the association between and impact of PIK3CA mutation status on disease-free survival (DFS) in HR+/HER2− early breast cancer patients. Methods. This cohort study was multicentric and retrospective in nature and was conducted at five Croatian institutions from July 2020 to December 2021. The study included initially early and locally advanced operable HR+/HER2− breast cancer patients who were diagnosed with disease recurrence during adjuvant hormonal treatment or within the first six years of follow-up. Results. A total of 186 patients were included, 40.9% of whom tested positive for the PIK3CA mutation. Primary and adjuvant treatment, particularly adjuvant endocrine treatment, were similar between the two groups. After adjustment for 14 relevant covariates, we found that patients with a positive PIK3CA status and the H1047 PIK3CA mutation had a significantly lower hazard of disease recurrence than patients with no PIK3CA mutation (HR 0.65; 95% CI 0.45; 0.95; p=0.024; false discovery rate, FDR <10%). Conclusions. This study highlights the potential impact of PIK3CA mutations on disease recurrence during or following adjuvant endocrine therapy and potentially opens the door for further investigation of possibly more personalized treatment strategies.